Factors Influencing Treatment Response in Patients with Malignant Otitis Externa: - Wongwan, Pithiwat; Thongyai, Kanthong; Atipas, Suvajana; Prakairungthong, Sarun; Limviriyakul, Siriporn; Suvarnsit, Kanokrat; Jenkins, Herman (Siriraj Medical Journal, 2025)
Objective: To identify factors affecting treatment outcomes in patients with malignant otitis externa (MOE). Materials and Methods: A retrospective review of MOE treatment was conducted in patients aged > 18 years admitted to Siriraj Hospital from January 2007 to December 2022. Predictors of treatment response chosen included duration of hospitalization, duration of antimicrobial treatment, disease-related re-admissions, and mortality. Results: The study included 49 patients (33 males, 16 females) with a mean age of 65±12 years. Comorbidities were present in 90% of patients, with diabetes mellitus being the most common. Pseudomonas aeruginosa was identified in 37% of cases. Bilateral symptoms/infections were reported in 18%. Facial nerve palsy and non-cranial nerve complications were 51% and 12%, respectively. Computed tomography (CT) imaging revealed bony erosion in 75%. Surgical management was performed in 73% of patients. The median duration of hospital stays and antimicrobial treatment were 34 days, and 143 days, respectively. Readmissions due to disease progression occurred in 35%, and the mortality rate was 4%. Bone erosion on CT was associated with an increased likelihood of readmission. Prolonged hospital stays were associated with bilateral symptoms and positive CT findings. Extended antimicrobial treatment was linked to multiple comorbidities, bilateral symptoms, non-cranial nerve complications, positive CT findings, and surgical cases. Conclusion: Various factors influence treatment outcomes in MOE patients. Early diagnosis, aggressive treatment, and management of prognostic factors are essential for preventing severe complications and improving survival outcomes.